The Role of Azacitidine in the Treatment of Elderly Patients with Acute Myeloid Leukemia: Results of a Retrospective Multicenter Study - (:unkn) unknown (GALENOS YAYINCILIK, 2016)
Objective: In this study, we aimed to investigate the efficacy and safety of azacitidine (AZA) in elderly patients with acute myeloid leukemia (AML), including patients with >30% bone marrow (BM) blasts. Materials and Methods: In this retrospective multicenter study, 130 patients of >= 60 years old who were ineligible for intensive chemotherapy or had progressed despite conventional treatment were included. Results: The median age was 73 years and 61.5% of patients had >30% BM blasts. Patients received AZA for a median of four cycles (range: 1-21). Initial overall response [including complete remission (CR)/CR with incomplete recovery/partial remission] was 36.2%. Hematologic improvement (HI) of any kind was documented in 37.7% of all patients. HI was also documented in 27.1% of patients who were unresponsive to treatment. Median overall survival (OS) was 18 months for responders and 12 months for nonresponders (p=0.005). In the unresponsive patient group, any HI improved OS compared to patients without any HI (median OS was 14 months versus 10 months, p=0.068). Eastern Cooperative Oncology Group performance status of <2, increasing number of AZA cycles (>= 5 courses), and any HI predicted better OS. Age, AML type, and BM blast percentage had no impact. Conclusion: We conclude that AZA is effective and well tolerated in elderly comorbid AML patients, irrespective of BM blast count, and HI should be considered a sufficient response to continue treatment with AZA.
Keywords: Azacitidine; Acute myeloid leukemia; Elderly; Bone marrow blasts; Prognostic factors; Overall survival; CONVENTIONAL CARE REGIMENS; INTERNATIONAL WORKING GROUP; ACUTE MYELOGENOUS LEUKEMIA; NEWLY-DIAGNOSED AML; OLDER PATIENTS; INTENSIVE CHEMOTHERAPY; MYELODYSPLASTIC SYNDROME; RESPONSE CRITERIA; AGE; CYTARABINE